Acceptance of AI in Journalism: A Tam Model Study on Digital Newsrooms in Indonesia - Dedi Prasetia; Bayu Tresna Riyadi; Irwansyah Irwansyah (Journal Of Social Science (JoSS), 2026)
The rapid development of artificial intelligence (AI) has accelerated the transformation of the global media industry, including the journalism ecosystem in Indonesia. AI integration into newsrooms has brought significant changes to news production, editing, and distribution, raising important questions about how journalists perceive and adopt this technology in their professional practice. This research explores the acceptance and use of artificial intelligence (AI) in journalistic practice by Indonesian journalists, using the Technology Acceptance Model (TAM) framework, which focuses on two constructs: perceived usefulness (PU) and perceived ease of use (PEOU). This study employs a qualitative descriptive approach with an intrinsic case study strategy to gain an in-depth understanding of journalists' experiences and perceptions. Data were collected through semi-structured, in-depth interviews with three digital news journalists who have used AI in their work processes, selected through purposive sampling. The interview data were analyzed using open, axial, and selective coding techniques to identify emerging themes and patterns. The study finds that AI is perceived as useful in accelerating editorial processes, text editing, and supporting SEO-based content production. AI is also considered relatively easy to learn, particularly through trial and error and peer assistance. However, AI adoption remains mediated by professional ethics, originality, and editorial autonomy. The findings indicate that AI integration in digital newsrooms involves not only technical efficiency but also social negotiation between productivity, ethics, and professional identity. This research contributes to the field of communication technology studies and offers practical implications for media management and editorial policy in age of automation.